Analysis of The Use of Modification Tools of Wave Jambu Fruit Skin (Anacardium Occidentale L) on The Quality of Jambu Mete - Kadir, Kadir; Baco, Abdu Rahman; Sakir, Sakir (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2020)
This study aims to determine the efficiency of the work efficiency of the tool by using a modification kacip, to determine the results of the quality of the cashew seeds produced with modified modifications determining the location of the study carried out intentionally (purposive) with respondents totaling 10 respondents. Data collection is done by interview and observation methods. Analysis of the data used design analysis with drawing rocks or skecap. The results of the analysis study were designed with two blades with 3 replications each time, large cashew fruit with an average of 0,3 kg /time, medium-size cashew with an average of 0,4 kg /time and small cashew fruit with an average of 0,31 kg /time, can be seen the working capacity of the equipment in tables 3, 4 and 5 with a total of 1,01 kg / time and an overall average of 0,33 kg /time. Whereas with one blade that has not been modified, with the working capacity of the tool in table 6. Large cashew fruit with an average of 0,25 kg /time, Medium cashew fruit with an average of 0,25 kg /time, and small cashew fruit with an average of 0,22 kg /time with an amount of 0,72 kg /time and an overall average of 0,24kg /time. To determine what percentage increase in working tools used by two blades and it turns out there is an increase in working tools with results 27.27%.